PENGEMBANGAN MEDIA MONOPOLI BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KECERDASAN EMOSIONAL - Nina Nabila; Evi Afiati; Siti Muhibah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop monopoly game media to enhance emotional intelligence based on Problem Based Learning. This research is based on the low emotional intelligence of grade XI students at SMAN 9 Tangerang Regency. The research method used is research and development (R&D) with the ADDIE model. The results of this study indicate that the emotional intelligence monopoly game media is feasible to use, supported by the media feasibility test results which obtained an average score of 87.2% with the category "very feasible", consisting of content and media test 75%, language expert test 92.85%, and practitioner test 93.75%. In a limited trial with 6 students, the average score was 81.84% with the category "feasible". In addition, the results of the pre-test and post-test showed an increase in students' emotional intelligence after being treated using Monopoly game media. Based on the results of the Wilcoxon Signed Rank Test, it was found that H₀ was rejected and Hₐ was accepted, thus the Monopoly game media is suitable to be used to improve students' emotional intelligence.